Myocardial fibrosis in rheumatic heart disease: emerging concepts and clinical implications - Putra, Teuku Muhammad Haykal; Rodriguez-Fernandez, Rodrigo; Widodo, Wishnu Aditya; Elfiana, Maria; Laksono, Sidhi; Nguyen, Quang Ngoc; Tan, Jack Wei Chieh; Narula, Jagat (Frontiers in Cardiovascular Medicine, 2023)
Rheumatic heart disease remains a significant cardiovascular burden in the world despite its decreased prevalence in developed countries. Rheumatic heart disease is frequently complicated by myocardial fibrosis. The presence of myocardial fibrosis holds a vital role in clinical aspects ofEmerging Concepts and Clinical Implications.Rheumatic heart disease (RHD) remains a significant cardiovascular burden in the world despite the fact that it is no longer common in affluent countries. Centuries of history surrounding this disease provide us with a thorough understanding of its pathophysiology. Infections in the throat, skin, or mucosa is the gateway for Group A Streptococcus (GAS) to penetrate our immune system. A significant inflammatory response to the heart is caused by an immunologic cascade triggered by GAS antigen cross-reactivity. This exaggerated immune response is primarily responsible for cardiac dysfunction. Recurrent inflammatory processes damage all layers of the heart, including endocardium, myocardium and pericardium. Vicious immunologic cycle involving Inflammatory mediators, angiotensin II, and TGF-β promotes extracellular matrix remodeling resulting in myocardial fibrosis. Myocardial fibrosis appears to be a prevalent occurrence in RHD patients. The presence of myocardial fibrosis, which causes left ventricular dysfunction in RHD, might be utilized to determine options of treatment and might also be used to predict outcome of interventions in RHD patients. This emerging concept of myocardial fibrosis need to be explored comprehensively in order to be optimally utilized in the treatment of RHD.